Kemampuan Pemahaman Isi Bacaan Pada Pembelajaran Bahasa Indonesia Di Kelas V Sdn Kuin Utara 7 - Ismi Khairun Nisa; Ahmad Suriansyah; Arta Mulya Budi Harsono; Rezky Amalia; Muhammad Ziyan Takhqiqi Arsyad (CV. ITTC INDONESIA, 2024)
This research was conducted with the aim of: first, to assess the current state of reading comprehension among elementary school students in general and fifth graders at SDN Kuin Utara 07. Second, explore and identify strategies to increase the ability to understand reading content. In this exercise, case studies serve as a foundation for the qualitative research methodology. Some methods of gathering information include observing classrooms and conducting interviews with instructors and students. All of the participants were fifth graders. The findings showed that some pupils struggled to comprehend the readings assigned to them, and that one student exhibited a lack of reading fluency. The factors causing this can be caused by external factors and also internal factors